FUNDAMENTALS OF IMPLEMENTING AN INSURANCE SYSTEM IN MEDICINE - Saidov Suhrob Shodmonovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT. Equity, efficiency, access, nutrition, and provider acceptability and quality are the cornerstones of universal health coverage (UHC). There is no single way to achieve effective UHC in any country. We focused on the challenges that are being faced in sustaining UHC.